Study on contents of nutrients and three environmental contaminants for 18 types of overseas online shopping infant formula - Jingsi CHEN; Ailian TAO; Jiansheng TANG; Jianhong LAO; Xiaofeng ZHOU; Feng LIN; Shuguang LI (Zhongguo shipin weisheng zazhi, 2020)
Objective To describe the content of nutrients and three environmental contaminants for "overseas online shopping" infant formulas. Methods 18 kinds of "overseas online shopping" infant formula and 14 kinds of domestically purchased infant formula were collected, and their nutritional composition and 3 environmental chemicals were analyzed and compared. Results Four kinds of "overseas online shopping" infant formula did not meet the GB 10765-2010, and the nutrient contents of "overseas online shopping" infant formulas were significantly different from those domestic purchased (P<0.05). The 5 main different indictors were energy (68.09, 66.77 kcal/100 mL), protein (2.00, 2.32 g/100 kcal), fat (5.51, 5.15 g/100 kcal), pantothenic acid (676.33, 910.84 μg/100 kcal), and iodin (20.60, 17.41 μg/100 kcal). Di-2-ethylhexyl phthalate (DEHP), bisphenol A (BPA) and perfluorooctanoic acid (PFOA) were not detected in any infant formula. Conclusion "Overseas online shopping" infant formulas did not completely meet the GB 10765-2010, further studies were needed to investigate the adaption of "overseas online shopping" infant formula to China's infants.